2016
DOI: 10.1016/j.carbpol.2016.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Lactobionic acid and carboxymethyl chitosan functionalized graphene oxide nanocomposites as targeted anticancer drug delivery systems

Abstract: In this work, we report a targeted drug delivery system built by functionalizing graphene oxide (GO) with carboxymethyl chitosan (CMC), fluorescein isothiocyanate and lactobionic acid (LA). Analogous systems without LA were prepared as controls. Doxorubicin (DOX) was loaded onto the composites through adsorption. The release behavior from both the LA-functionalized and the LA-free material is markedly pH sensitive. The modified GOs have high biocompatibility with the liver cancer cell line SMMC-7721, but can i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(36 citation statements)
references
References 53 publications
3
33
0
Order By: Relevance
“…It is clear that the GO nanosheets exhibited an extended thin film with a wrinkled surface, which prevented the collapse of GO back into a graphite structure [ 23 ]. The cross-sectional view towards the AFM image of the exfoliated GO ( Figure 1 c,e) shows that GO presented an ultrathin lamellar structure with a height of 0.5–1 nm, which is consistent with the reported thickness of GO in previous AFM studies [ 24 ].…”
Section: Resultssupporting
confidence: 88%
“…It is clear that the GO nanosheets exhibited an extended thin film with a wrinkled surface, which prevented the collapse of GO back into a graphite structure [ 23 ]. The cross-sectional view towards the AFM image of the exfoliated GO ( Figure 1 c,e) shows that GO presented an ultrathin lamellar structure with a height of 0.5–1 nm, which is consistent with the reported thickness of GO in previous AFM studies [ 24 ].…”
Section: Resultssupporting
confidence: 88%
“…The nanocarrier has induced cell death after 24 hrs of incubation and shown higher biocompatibility with liver cancer cell lines. 40 Yuan et al, 2015 indicated that a combination of folic acid, monoclonal antibodies and gold nanoparticles-based graphene nanocomposites promoted HepG2 cell apoptosis with drug targeting and controlled release properties. 41 Polylactic-Co-Glycolic Acid (PLGA) Nanoparticles…”
Section: Inorganic Nanocarriersmentioning
confidence: 99%
“…54 Lactobionic acid (LA), comprising gluconic acid and Gal moiety, is the common ligand for hepatoma-targeted delivery. [55][56][57] The Gal residues on drug delivery system can recognize and bind specifically to the ASGPR on the hepatoma cells, 58,59 thus they facilitate drug delivery into the cells, which are inhibited and killed by therapeutic agents in delivery vehicles. Zhong's group developed a series of Gal-directed hepatoma-targeting delivery system to enhance the accumulation of anticancer drugs into and antitumor activity toward hepatoma cells.…”
mentioning
confidence: 99%